The vascular wall in postmenopausal women with hypothyroidism and hypertension - O Iu Riabtseva; Ia A Orlova; Z N Blankova; T E Chazova; F T Ageev (Терапевтический архив, 2013)
AIM: To study a relationship between thyroid function and the stiffness of great arteries in postmenopausal women with arterial hypertension (AH)/MATERIAL AND METHODS: The trial enrolled 76 postmenopausal patients with clinical hypothyroidism (CHT) (n=24) or subclinical hypothyroidism (SCHT) (n=52) and AH; a control group consisted of 40 postmenopausal women with euthyroidism. Body mass index (BMI), waist and hip circumferences, blood pressure (BP), thyroid-stimulating hormone (TSH), free thyroxine, free triiodothyronine, total cholesterol, triglycerides were determines; volumetric sphygmography was performed. Brachial-ankle pulse wave velocity (baPWV) was measured; cardio-ankle vascular index (CAVI) and ankle-brachial index (ABI) were determined/RESULTS: The patients with CHT or SCHT and the controls were matched for age, BMI, BP, and heart rate. TSH levels in patients with SCHT (6.23 (5.27; 8.22) µU/ml) and in those with CHT (11.8 (9.09; 22.7) µU/ml) were statistically significantly higher than in the control group (2.25 (1.5; 2.72) µU/ml) (p